The concept of aerotropolis applied to a medium-sized city and its airport - Carmo, João Jóia do (2020)
Movements in Faro airport have been on a constant rise even exceeding the airport capacity. Faro city has grown in the same proportion. Both occurred in a pattern that can be applied to compare with the development of an Aerotropolis. At least three steps must be taken to develop an eﬀective Aerotropolis plan. First, the catchment area is determined based on the existing transportation network and 60-minute travel time from the airport. Second, several socioeconomic indicators within the catchment area are evaluated through diﬀerent periods using GIS software. Third, catchment area and socioeconomic indicators for the Faro region are compared with layouts obtained from several examples of Aerotropolises in Europe. The Aerotropolis model created by John Kasarda has been used in several regions across Europe. One key aspect of this model is determining whether the region evolved along with the airport throughout the years. Faro, its airport and surrounding areas, are not an exception. Thus, it is possible to identify Faro development patterns of growth useful for several stakeholders: administrative authorities, airport authorities, and territory planners. Faro airport movements have been on a constant rise. Faro city has grown, probably, in the same proportion. Both growths can be compared with an Aerotropolis development. Identifying development patterns of growth will be useful for: those responsible for the distribution of services in the territory; those who oversee the airport operation and expansion; those who are responsible for combining the interests of all for the regional development.